Between Beneath Before and Beyond : An Exploration of the Human Condition based on Paul Ricoeur 1913-2005 - Kuruvilla Pandikattu; PANDIKATTU (Kuruvilla ) (Pune Creati Ventures, 2013)
This book explores the dynamic, tensional and transcending nature of human beings. the first part, HUMAN FECUNDITY, deals with the human being as story-teller, myth-maker and dreamer. The second part, HUMAN FRAILTY, reflects on the tension and dilemma in human experience. The third part, HUMAN FALLIBILITY, sees human person as sinner, forgiver and prayer. Finally, we reflect on human nature as the tensional and enriching journey from the past to the future, from the actual to the potential, from the symbolic to the mythic and from the real to the creative.
Keywords: Philosophical anthropology